New, Non‐quinone Fluorogeldanamycin Derivatives Strongly Inhibit Hsp90. Issue 2 (8th January 2015) - Hermane, Jekaterina; Bułyszko, Ilona; Eichner, Simone; Sasse, Florenz; Collisi, Wera; Poso, Antti; Schax, Emilia; Walter, Johanna‐Gabriela; Scheper, Thomas; Kock, Klaus; Herrmann, Christian; Aliuos, Pooyan; et al.
Abstract Streptomyces hygroscopicus is a natural producer of geldanamycin. Mutasynthetic supplementation of an AHBA‐blocked mutant with all possible monofluoro 3‐aminobenzoic acids provided new fluorogeldanamycins. These showed strong antiproliferative activity and inhibitory effects on human heat shock protein Hsp90. Binding to Hsp90 in the low nanomolar range was determined from molecular modelling, AFM analysis and by calorimetric studies.